"African Factors" in the Metamorphosis of Indigenous Pentecostalism in Ekitiland, Nigeria - Tokunbo, Bankole (Black theology, 2019)
Pentecostalism is a renewal movement within Christianity that places primary emphasis on gifts of the Holy Spirit, joyful worship, exorcism and discourse on prosperity and the "born again" experience. African Pentecostalism is a segment of African Christianity that is proliferating at an exponential rate. It is the most widespread form of non-Roman Catholic Christianity in Africa today. In Ekitiland, which is predominantly a Christian milieu, indigenous Pentecostalism has become an increasingly prominent feature in the religious and political landscape of Ekiti-kete. The growth of indigenous Pentecostalism in Ekiti Communities has been particularly dramatic since the 1980s. Suffice it to say that, much of the worldviews underlying the important expressions of indigenous Pentecostalism in Ekiti communities like healing, "deliverance" exorcism and belief in spirits resonate with traditional African philosophical thoughts. This is an important factor that contributes to the growth of Indigenous Pentecostal Churches (IPCs) in Ekitiland.